2018
DOI: 10.3847/1538-4357/aac6c8
|View full text |Cite
|
Sign up to set email alerts
|

High-contrast Polarimetry Observation of the T Tau Circumstellar Environment

Abstract: We conducted high-contrast polarimetry observations of T Tau in the H-band, using the High Contrast Instrument for the Subaru Next Generation Adaptive Optics instrument mounted on the Subaru Telescope, revealing structures as near as 0 1 from the stars T Tau N and T Tau S. The whole T Tau system is found to be surrounded by nebulalike envelopes, and several outflow-related structures are detected in these envelopes. We analyzed the detailed polarization patterns of the circumstellar structures near each compon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Additionally, interaction of a wind from T Tau Sa with the circumbinary ring might play an extra role in increasing the diameter of the dynamically cleared ring cavity, as gas and dust are slowly eroded by the wind. High spatial resolution, high contrast near-IR maps of T Tau from Yang et al (2018) revealed evidence for small dust grains that appeared to be streaming toward the west of T Tau S. Particularly, we postulate that the "N3" and "N4" arcs of H-band polarimetric emission identified by Yang et al (2018) could be evidence of small dust grains streaming westward from the circumbinary ring after being eroded by a wide angle wind from T Tau Sa.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Additionally, interaction of a wind from T Tau Sa with the circumbinary ring might play an extra role in increasing the diameter of the dynamically cleared ring cavity, as gas and dust are slowly eroded by the wind. High spatial resolution, high contrast near-IR maps of T Tau from Yang et al (2018) revealed evidence for small dust grains that appeared to be streaming toward the west of T Tau S. Particularly, we postulate that the "N3" and "N4" arcs of H-band polarimetric emission identified by Yang et al (2018) could be evidence of small dust grains streaming westward from the circumbinary ring after being eroded by a wide angle wind from T Tau Sa.…”
Section: Discussionmentioning
confidence: 77%
“…However, a new generation of extremely sensitive high contrast adaptive optics imaging has challenged the outflow geometry found from the past kinematic measurements. Particularly, Herbst et al (2007) and Yang et al (2018) measured high contrast near-IR H 2 and H-band polarized continuum, respectively, and found evidence that T Tau Sa or Sb may be driving a western component of the outflows, previously attributed to T Tau N. As observations of the inner environment of T Tau have improved and become more sensitive, confusion in the orientation and nature of the outflows from the system has followed.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The T Tau N disk was found to be a bright disk with a total flux of ∼ 180 mJy at 1.3 mm, but is only seen as a flat compact disk with a radius of ∼ 20 au. Similarly, neither ground-based near-infrared adaptive optics observations nor space-based optical observations can resolve the disk around T Tau N and T Tau Sa/Sb well with a resolution of ∼ 0 .07 or 10 au (e.g., Yang et al 2018). Intriguingly, Manara et al (2019) pointed out that significance residuals (∼ 3σ) were found both at the T Tau N and T Tau S after subtracting axisymmetric models of the two sources from the ALMA continuum image.…”
mentioning
confidence: 99%